Navy boys to the rescue - Davidson, Halsey; Angell, Clare, 1874-1932 (Salt Lake City, UT : Project Gutenberg, 2024)
"Navy Boys to the Rescue: Answering the Wireless Call for Help" by Halsey Davidson is a fictional adventure novel written in the early 20th century. The story follows a group of young sailors from the United States Navy, known as the Navy Boys, as they encounter various challenges and enemies during World War I while on patrol duty. The main characters include Phil Morgan, also known as Whistler, and his friends Alfred Torrance, Michael Donahue, and Ikey Rosenmeyer, as they navigate their adventures on the destroyer "Colodia". The opening of the story introduces the Navy Boys on shore leave in England, enjoying their time away from the ship and engaging in lively banter. However, their peaceful outing is interrupted when they come across a British sailor in a precarious situation with an American lad, George Belding, who is being held against his will by the intoxicated sailor. The Navy Boys quickly decide to intervene and attempt to rescue Belding, setting the stage for the excitement and action that follows. The narrative hints at an overarching theme of camaraderie and bravery that the boys will need to display as they face further trials, particularly with the arrival of a German Zeppelin overhead. (This is an automatically generated summary.)
Release date is 2024-01-15
Roger Frank and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images made available by the Library of Congress)
Keywords: World War, 1914-1918 -- Naval operations -- Juvenile fiction; United States. Navy -- Juvenile fiction